2013
DOI: 10.1371/journal.pone.0059335
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Target of Rapamycin (mTOR) Activity Dependent Phospho-Protein Expression in Childhood Acute Lymphoblastic Leukemia (ALL)

Abstract: Modern treatment strategies have improved the prognosis of childhood ALL; however, treatment still fails in 25–30% of patients. Further improvement of treatment may depend on the development of targeted therapies. mTOR kinase, a central mediator of several signaling pathways, has recently attracted remarkable attention as a potential target in pediatric ALL. However, limited data exists about the activity of mTOR. In the present study, the amount of mTOR activity dependent phospho-proteins was characterized by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 46 publications
(54 reference statements)
0
31
0
Order By: Relevance
“…Notably, these mutations are strongly associated with poorer outcomes in both children and adults . Empirical evidence has also shown a direct correlation between AKT and/or mTOR activation and poor prognosis in patients with paediatric and adult B‐ALL .…”
Section: Introductionmentioning
confidence: 99%
“…Notably, these mutations are strongly associated with poorer outcomes in both children and adults . Empirical evidence has also shown a direct correlation between AKT and/or mTOR activation and poor prognosis in patients with paediatric and adult B‐ALL .…”
Section: Introductionmentioning
confidence: 99%
“…1 m TOR signaling is elevated in both T-cell and B-cell ALL and correlates with high risk of relapse and resistance to chemotherapy regimens. 2 targeted agents. 5,6 However, the mechanisms by which mTOR dual inhibitors promote ALL cell death have not been established.…”
mentioning
confidence: 99%
“…Elevated mTOR signaling was reported to correlate with poor prognosis in B-ALL patients [75]. However, no knockout mouse disease models for mTORC1 or mTORC2 to study B-ALL in mice was reported.…”
Section: B-all and Other Hematologic Malignanciesmentioning
confidence: 99%